Analisis Efektifitas Penerimaan Pajak Bea Perolehan Hak Tanah Bangunan Daerah Kota Ambon Periode 2018-2022 - Anna Valensia Christianty De Fretes (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to measure the level of effectiveness of taxes on the acquisition of rights to land and buildings in the Ambon City area for the 2018-2022 period. This research is the first regarding the Effectiveness of Ambon City Regional BPHTB Taxes. This type of research is quantitative descriptive research using Effectiveness Ratio Analysis and measurements based on Effectiveness Categories according to Decree of the Minister of Home Affairs No. 690,900,329 of 2006. The results of this research show that the level of revenue is less effective in the 2019 and 2022 periods due to the Covid-19 Pandemic and Budget Targets that are less effective. very high compared to previous periods. However, it can be said to be very effective in 2018 and 2021 because acceptance reached 100% or >100%. In the 2020 period it is said to be ineffective because the presentation level based on the Effectiveness Ratio and Effectiveness Criteria is below or <60%, this is purely due to the Covid-19 pandemic and government policy in carrying out activities as before.